Separation of State Assets in State-Owned Enterprises from State Liability for Losses - Mulyono Dwi Purwanto; Tuti Widyaningrum (Utan Kayu Publishing, 2025)
The issue of state finance and the separation of state assets in SOEs lies at the intersection of criminal law on corruption, state financial law, and state corporate law, so that the relationship between regimes must be arranged so that corporate losses are not automatically treated as state losses or vice versa. The reform of the 2025 SOE Law emphasizes corporate autonomy that is supervised through audits and the principle of lex specialis. Research Objectives Analyze the legal status of separated state assets in SOEs within the framework of state finances and examine the effect of such separation on the limits of liability for state losses. The research method used is normative juridical based on secondary data with a statutory and conceptual approach. Data were collected through a literature study of the 1945 Constitution, the Corruption Law, the State Finance Law, the 2025 SOE Law, and decisions, then analyzed qualitatively. Research Results The status of separated assets is layered on the horizon of permanent ownership including state finances according to Law 17/2003, while on the horizon of management it becomes corporate capital according to Law 1/2025 in conjunction with Law 16/2025 and the principles of good corporate governance. Losses from state-owned enterprises (SOEs) transform into state losses if they are proven to have reduced state fiscal capacity due to fiduciary violations outside the business judgment rule. Furthermore, the separation of assets creates a multi-layered accountability regime based on fault-based liability and positions the SOE Law as a lex specialis, requiring both corporate and fiscal tests before the Corruption Eradication Law is applied as the ultimum remedium.